Measurement of the ZZ production cross section and Z -> l(+)l(-)l '(+)l '(-) branching fraction in pp collisions at root s=13TeV - (:unkn) unknown (ELSEVIER, 2016)
Four-lepton production in proton-proton collisions, pp -> (Z/gamma*)(Z/gamma*)-> l(+)l(-)l '(+)l '(-), where l,l '(-) = e or mu, is studied at a center-of-mass energy of 13 TeV with the CMS detector at the LHC. The data sample corresponds to an integrated luminosity of 2.6fb(-1). The ZZ production cross section, sigma(pp -> ZZ) = 14.6(-1.8)(+1.9)(stat)(-0.3)(+0.5) (syst) +/-0.2 (theo) +/-0.4 (lumi) pb, is measured for events with two opposite-sign, sameflavor lepton pairs produced in the mass region 60 < m(l+l-) m (l'+l'-) < 120GeV. The Z boson branching fraction to four leptons is measured to be B(Z -> l(+)l(-)l '(+)l '(-)) = 4.9(-0.7)(+0.8)(stat)(-0.2)(+0.3)(syst)(-0.1)(+0.2)(theo) +/- 0.1 (lumi) x10(-6) for the four-lepton invariant mass in the range 80 < m(l+)l-l'+l' < 100GeVand dilepton mass m(l+l-) > 4GeVfor all opposite-sign, same-flavor lepton pairs. The results are in agreement with standard model predictions. (C) 2016 The Author. Published by Elsevier B. V. This is an open access article under the CC BY license
Keywords: CMS; Physics; Electroweak